Female adnexal tumor of probable Wolffian origin - Arvind K Gupta; Radhika Srinivasan; Raje Nijhawan (Wolters Kluwer Medknow Publications, 2014)
Female adnexal tumor of probable Wolffian origin (FATWO) is a rare neoplasm arising from the remnants of the mesonephric duct. We report here a case of FATWO in a 70-year-old woman arising from the broad ligament and confirmed on immunohistochemistry. Most of these tumors behave in a benign fashion but certain histological features like hypercellularity, cellular pleomorphism and nuclear atypia as seen in the index case may increase the rate of recurrence and metastasis. Therefore, close follow-up is recommended for FATWO.